Avaliação das propriedades do compósito de matriz polimérica ortoftálica com fibra de sisal e resíduos de escória de alto-forno - DIAS, Andreza Karen Brioso (2024)
This study promoted the production of polymer composites using waste blast furnace slag, sisal fiber and hybrid composites. The objective is to evaluate the physical, mechanical, fractographic and flammability properties of these materials. The manufacturing was carried out manually in a silicone mold, without compression, with the insertion of 1% of initiator in the mixture with the polymeric matrix, with natural sisal fibers (1%, 2% and 3%) and high-quality slag residues. oven (10%, 20% and 30%). The hybrid composites were manufactured with mass fractions of 20% waste and 2% sisal fibers. Apparent specific mass tests and morphological characterization of both the residue and fiber were carried out, and mineralogical characterizations of the residue were also carried out. After manufacturing the specimens, physical tests were conducted to determine water absorption, apparent porosity and apparent specific mass, followed by the mechanical tensile strength test, with fracture surface analysis carried out by scanning electron microscopy and the rate flame propagation was evaluated using the horizontal flammability test. The analyzes revealed that sisal fiber has a specific mass of 1.295 g/cm³, while blast furnace slag registers 3.013 g/cm³, values consistent with the literature. Morphological and mineralogical analyzes of the waste highlighted characteristics that can influence the properties of the composites, such as the size and shape of the particles, as well as the presence of the mineral quartz. In physical tests, a reduction in porosity and water absorption was observed compared to the full matrix. On the other hand, composites with sisal fiber showed an increase in porosity and water absorption due to the natural porosity of the fiber. The specific mass of the composites increased with the introduction of reinforcements in the matrix. The tensile test revealed that the composite with 3% sisal fiber had the highest resistance, reaching 33.598 MPa. The analysis of the fracture surface of the composites revealed the failure mechanisms associated with mechanical resistance. The horizontal flammability test classified the materials as HB (Horizontal Burning), flame resistance criteria standard, of the ASTM D 635 standard. The composition with 30% blast furnace slag obtained results, with a reduction of 76.71%, in relation to the CONTRAN 498 standard.